Determinants of Household Financial Management: Literacy, Attitudes, and Income - Magribi, Robi Maulana; Ginanjar, Yogi; Rusdiana, Alan; Utami, Indira (Finance and Business Management Journal, 2025)
Household financial management involves the regulation of family income, expenditures, investments, and savings as a mechanism to achieve both short-term and long-term financial goals. Deficiencies in the application of financial literacy, sound financial attitudes, and adequate income levels can expose individuals to risks such as online loans, non-performing credit, and even divorce, largely stemming from a lack of understanding in managing household finances. The purpose of this study is to identify the impact of Financial Literacy, Financial Attitudes, and Income on Household Financial Management. This study adopts a quantitative research approach with a focus on descriptive and verificative analysis. The research population consists of all households of student guardians at TKIT Al Muyassar, Cigasong District, Majalengka Regency. Sampling was conducted using a non-probability sampling technique with a saturated sampling method, resulting in a sample of 30 respondents. The analytical techniques applied include multiple linear regression, the coefficient of determination test, and hypothesis testing. The results of this study indicate that Financial Literacy has a significant effect on Household Financial Management. Financial Attitude has a significant effect on Household Financial Management. Income has a significant effect on Household Financial Management.